MONITORING DAN EVALUASI KARTU JAKARTA PINTAR (KJP) PLUS DI WILAYAH JAKARTA PUSAT - Noor, Dani Vardiansyah; Fajarina, Fajarina (Universitas Esa Unggul, 2019)
AbstractIn connection with the dropout rate in DKI Jakarta caused by the poverty level, the DKI Jakarta government in December 2012 has released a new program called the Jakarta Smart Card (KJP), which is one of the Personal Education Funding Assistance. With this policy, the Jakarta Government provides access for DKI Jakarta residents who cannot get education at least up to Senior High Schools or Vocational Schools. This assistance is fully supported by DKI Jakarta's national income. The aim of the Jakarta Smart Card program is considered as an effort to improve the community, especially students who come from families who need to complete 12-year compulsory education in DKI Jakarta. The purpose of this community service is to find out the implementation of KJP policies in the Central Jakarta region in 2018 and also to find out the constraints and supporting factors of this policy. The results of the policy evaluation indicate that the KJP Policy for the Central Jakarta region has not been successful. Therefore, there are many differences between normative goals and empirical situations in society. This mismatch occurs because of constraints in KJP implementation. For example: (1) the lack of human and financial resources to support the KJP Program for the period 2018, (2) the process of selecting SKJ-based KJP recipients and photographic evidence involving some misunderstandings of students as recipients. incompetent even though they already have SKTM and photographic evidence, (3) the distribution of KJP funds in 2018 has been delayed because there are still many schools that propose KJP programs outside of school records and that causes multiple account problems, (4) lack of observations for this program either from school or Education Services.Ã‚Â Keywords: monitoring,evaluation, jakarta smart card (KJP) Ã‚Â AbstrakSehubungan denganangka putus sekolah di DKI Jakarta yang disebabkan oleh tingkat kemiskinanmaka pemerintah DKI Jakarta pada Desember 2012 telah merilis program baru yang disebut dengan Kartu Jakarta Pintar (KJP) yang merupakan salah satu Bantuan Pendanaan Pendidikan Pribadi. Dengan kebijakan ini, Pemerintah Jakarta memberikan akses bagi wargaDKI Jakarta yang tidak bisa mendapatkan pendidikan setidaknya sampai SekolahMenengah Atas atau Sekolah Kejuruan. Bantuan ini sepenuhnya didukung oleh pendapatan nasionalDKI Jakarta. Tujuan dari program Kartu Jakarta Pintar dianggap sebagai upaya untuk meningkatkan masyarakat terutama siswa yang berasal dari keluarga yang membutuhkan untuk menyelesaikan wajib belajar 12 tahun di DKI Jakarta.Adapun tujuan dari pengabdian masyarakat ini adalah untuk mengetahui implementasi kebijakan KJP di wilayah Jakarta Pusat pada tahun 2018 dan juga untuk mengetahui kendala dan faktor pendukung dari kebijakan ini. Hasil evaluasi kebijakan menunjukkan bahwa Kebijakan KJP untuk wilayah Jakarta Pusat belum berhasil. Karena itu ditemukan banyak perbedaan antara tujuan normatif dan situasi empiris dalam masyarakat. Ketidaksesuaian itu terjadi karena kendala dalam implementasi KJP. Faktor-faktor yang menjadi kendala dalam Program KJP di Jakarta Pusat misalnya: (1) kurangnya sumber daya manusia dan keuangan untuk mendukung Program KJP untuk periode 2018, (2) proses pemilihan penerima KJP berbasis SKTMdan bukti foto melibatkan beberapa kesalahpahaman siswa sebagai penerima yang tidak kompeten walaupun mereka sudah memiliki SKTM dan bukti foto, (3) distribusi dana KJP pada tahun 2018 mengalami keterlambatan karena masih banyak sekolah yang mengusulkan program KJP di luar catatan sekolah dan itu menyebabkan masalah akun ganda, (4) kurangnya pengamatan untuk program ini baik dari sekolah atau Layanan Pendidikan.Ã‚Â Kata kunci : monitoring, evaluasi, kartu jakarta pintar (KJP)